Conflict at work, job embeddedness, and their effects on intention to quit among women employed in travel agencies: Evidence from a religious city in a developing country. (20th December 2017) - Khorakian, Alireza; Nosrati, Saeid; Eslami, Ghasem
Abstract: Intention to quit is an important concern in organizations active in the tourism industry. This issue is more evident among the employed women in religious developing countries due to the cultural and environmental conditions. This study aimed to examine the mediating role of job embeddedness and the antecedents including work–leisure conflict, work–family conflict, and work overload on intention to quit. Data were collected from 618 female employees working in travel agencies. The results showed that the negative effects on the work‐leisure conflict, work‐family conflict and work overload led to a reduction in job embeddedness and an increase in their intention to quit.